Case Report: Autoimmune glial fibrillary acidic protein astrocytopathy complicated with Sjogren’s syndrome and recurrent respiratory failure - Chen, Po-You; Lee, Tzu-Han; Tsai, Wan-Lun; Chang, Hua-Ren; Tseng, Kuo-Sen; Wu, Cheng-Che (Frontiers in Immunology, 2025)
Autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy (GFAP-A) is a recently identified autoimmune encephalitis. We reported a case of a male in his 50s with autoimmune GFAP-A complicated with Sjogren’s syndrome and recurrent respiratory failure. The patient presented with acute and disabling encephalitis and myelitis, with symptoms including respiratory failure, swallowing dysfunction and limbs weakness. Autoimmune tests showed elevated GFAP and positive antinuclear antibody, anti-Ro and anti-Smith antibodies. MRI revealed longitudinal hypersignal from the anterior medulla to the C1 spinal cord. The clinical symptoms were favorably improved by steroid treatment and rehabilitation training. This case highlighted the spectrum of clinical manifestations associated with GFAP-A. Our findings also supported the effectiveness of rehabilitation training in treating this disease. Further investigation regarding diagnostic criteria, imaging characteristics, and the role of rehabilitation training in treating GFAP-A is necessary. This case was presented herein to shed more light on various aspects of this disease.